2021
DOI: 10.1038/s41746-021-00486-5
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health strategies for blood pressure self-management in urban populations with digital barriers: systematic review and meta-analyses

Abstract: Mobile health (mHealth) technologies improve hypertension outcomes, but it is unknown if this benefit applies to all populations. This review aimed to describe the impact of mHealth interventions on blood pressure outcomes in populations with disparities in digital health use. We conducted a systematic search to identify studies with systolic blood pressure (SBP) outcomes located in urban settings in high-income countries that included a digital health disparity population, defined as mean age ≥65 years; lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 74 publications
3
40
0
Order By: Relevance
“…A recent review investigated the effectiveness of mobile health apps for blood pressure management in populations with digital barriers, among other older adults. The authors confirmed the promise of ATs for chronic disease management but also emphasized the need for more studies including vulnerable populations [ 57 ]. The willingness for and success of AT-supported self-management can also be dependent on the disease [ 59 ].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…A recent review investigated the effectiveness of mobile health apps for blood pressure management in populations with digital barriers, among other older adults. The authors confirmed the promise of ATs for chronic disease management but also emphasized the need for more studies including vulnerable populations [ 57 ]. The willingness for and success of AT-supported self-management can also be dependent on the disease [ 59 ].…”
Section: Discussionmentioning
confidence: 66%
“…Only 19 RCTs fulfilled the inclusion criteria. The selected trials were very heterogeneous with respect to the ATs applied as well as the outcomes, which made it difficult to summarize the evidence [ 57 ]. Our analysis did not provide strong confirmation for the overall effectiveness of AT in older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSMonitor also provides the opportunity to target persons at risk of developing hypertension through personalized decision support, education, and coaching that are pivotal to avoid or delay disease onset and progression. Hypertension is a highly prevalent disease, and although relatively easy ease to treat, it shows heterogeneous outcomes that are influenced by educational background, ethnicity, and age that, for example, can hinder access to primary care [ 29 ]. mHealth solutions such as HSMonitor can play a crucial role in addressing some of these inequalities, providing the opportunity for remote management and telemonitoring that have already proved effective for such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile technology presents an opportunity to reduce financial, geographic, and workforce barriers, but little data currently support its use in populations with digital disparities 2 . A recent article by Khoong et al 3 . systematically reviews the literature to quantify outcomes for these populations and provide a roadmap toward more inclusive mobile health strategies.…”
mentioning
confidence: 99%